2018
DOI: 10.1017/mdh.2018.5
|View full text |Cite
|
Sign up to set email alerts
|

‘A Wicked Operation’? Tonsillectomy in Twentieth-Century Britain

Abstract: Histories of twentieth-century surgery have focused on surgical ‘firsts’ – dramatic tales of revolutionary procedures. The history of tonsillectomy is less glamorous, but more widespread, representing the experience and understanding of medicine for hundreds of children, parents and surgeons daily. At the start of the twentieth century, tonsillectomy was routine – performed on at least 80 000 schoolchildren each year in Britain. However, by the 1980s, public and professional discourse condemned the operation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…21 Consequently, by the late 1960s, tonsillectomy was predominantly performed to prevent acute tonsillitis, rather than to prevent secondary streptococcal infections throughout the body. 22…”
Section: Resultsmentioning
confidence: 99%
“…21 Consequently, by the late 1960s, tonsillectomy was predominantly performed to prevent acute tonsillitis, rather than to prevent secondary streptococcal infections throughout the body. 22…”
Section: Resultsmentioning
confidence: 99%
“…16,17 As surgical safety improved, full tonsillectomy became established as the standard technique and was performed on a huge number of children in the post-war era. 17 With the improving general health of the paediatric population and attempts to reduce health care budgets, the number of tonsillectomies performed worldwide for recurrent tonsillitis has significantly reduced with sleep-disordered breathing emerging as the main diagnosis for consideration of tonsil surgery. 1,2 As the indications for surgery transformed, in the 1980s in Sweden, subtotal tonsil surgery emerged again as a potentially safer option to a full tonsillectomy for the relief of pharyngeal obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Subtotal tonsil surgery was actually performed commonly in the early part of the 20th century when haemorrhage rates for complete tonsillectomy were unacceptably high, largely due to poor methods of haemostasis 16,17 . As surgical safety improved, full tonsillectomy became established as the standard technique and was performed on a huge number of children in the post‐war era 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported it is possible to recover MTBC DNA from the oral cavity of individuals with bacteriologically confirmed TB [ 3 , 4 , 5 ]. Although this is an unusual location, MTBC was frequently detected from the tonsils and adenoids of individuals undergoing tonsillectomies in the 19th and 20th centuries, and was proposed as a method to assess the prevalence of TB in the 1930s, and thus the presence of MTBC in the mouth is biologically plausible [ 6 ].…”
Section: Introductionmentioning
confidence: 99%